Kolaborasi Guru BK, Guru Pendidikan Agama Islam dan Wali Kelas dalam Mengatasi Perilaku Bermasalah Siswa - Nurhanifah Harahap; Rapisa Putri Ayu; Tiya Desmita; Hidayani Syam (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Collaboration between Counseling Guidance Teachers (BK), Islamic Religious Education Teachers (PAI), and Homeroom Teachers has a strategic role in overcoming students' problematic behavior in the school environment. Students' problematic behaviors, such as lack of discipline, violation of rules, and conflicts between students, require holistic and integrated handling. The counseling teacher is in charge of providing psychological guidance and character development for students, the PAI teacher plays a role in instilling religious and moral values, while the homeroom teacher serves as the main liaison between students, parents, and the school. This collaboration involves identifying problems, developing treatment strategies, and implementing interventions that suit students' needs. Collaboration methods include planned discussions, case analysis, and coaching programs that are educative and rehabilitative in nature. With this synergy, schools are able to create a conducive learning environment, help students develop their best potential, and prevent the recurrence of problematic behavior. This research is expected to contribute to improving the quality of education services and building students' character with integrity.